THE EFFECT OF SERVICE QUALITY AND FACILITIES ON PUBLIC SATISFACTION IN DINAS PERPUSTAKAAN KOTA TEBING TINGGI - Sri Rahayu; Sri Indah Lestari; Cornelius Ricardo; Aisyah Siregar; Lukieto Cahyadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to determine the influence of service quality and facilities on community satisfaction at the Tebing Tinggi City Library. The research method used is a quantitative method using SPSS version 25.00, which was collected from the results of interviews with visitors to the Tebing Tinggi City Library as many as 98 respondents. The analytical method used in this research is using instrument tests, namely validity and reliability tests. Classic assumption tests are normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing namely T test and path analysis. The results of SPSS in this research are that the service quality variable influences community satisfaction, facilities influence community satisfaction, service quality and facilities simultaneously influence community satisfaction.